Delayed Traumatic Diaphragmatic Hernia Presenting as Pneumothorax: A Case Report - Iman Hakim Wicaksana; Suryo Wahyu Raharjo (HM Publisher, 2025)
Traumatic diaphragmatic hernias (TDHs) are a serious complication of both blunt and penetrating trauma, often requiring prompt surgical intervention. While most TDHs present acutely, a subset of cases may have a delayed presentation, posing diagnostic and management challenges. This case report describes a 66-year-old woman who developed a delayed left-sided TDH following a motor vehicle accident, initially misdiagnosed as pneumothorax. A 66-year-old female presented to our hospital with complaints of severe left-sided chest pain and progressive dyspnea four days after a motor vehicle accident. Initial assessment at another hospital revealed rib fractures and pneumothorax, for which a chest tube was inserted. However, her respiratory symptoms persisted, prompting further evaluation. A chest X-ray and subsequent thoracoabdominal CT scan revealed a large left-sided diaphragmatic hernia with herniation of abdominal viscera into the thoracic cavity. The patient underwent emergency laparotomy and diaphragmatic hernia repair with primary closure. Postoperatively, the patient's symptoms improved significantly, and she was discharged home with complete resolution of her complaints. In conclusion, this case highlights the importance of maintaining a high index of suspicion for TDH in patients with a history of trauma, even in the absence of initial suggestive findings. Delayed presentation of TDH can occur, and a thorough evaluation, including imaging studies, is crucial for accurate diagnosis and timely management.